An Approximation to the Problem of the Free will - Baquer Estrada, Divaldo (Disertaciones, 2017)
The article tries to introduce the reader to the problem free will, showing the apparent contradiction between two plausible ideas. First is the idea that everything that happens in this universe is caused or determined by previous events or circumstances (Determinism). Secondly, the idea that human beings are free to do or not do what want, without being causally determined to do (Libertarianism). Finally, I will defend a third point of view that comes trying to reconcile the two ideas earlier, which says that determinism and libertarianism are not contradictory, since we can be considered morally responsible for our despite free elections to be determined (Compatibilism).
Keywords: Free will; Determinism; Libertarianism; Compatibilism; Free Acts; Non-Free Acts